Analysis of coupling factors between high proportion wind power and ultra-high voltage DC. (October 2020) - Fan, Guowei; Fan, Guoqi; Song, Pengfei; Ren, Chong; Kang, Pengpeng; Cheng, Lin; Zhang, Facai
Abstract: Due to the imperfect construction of supporting thermal power units, when wind power sources are in full swing, if DC low-power operation will inevitably lead to wind power abandonment, if DC high power operation is subject to fault transient overvoltage operation constraints, it will also cause power curtailment of wind power sources. In order to promote wind power consumption and lean management of DC influencing factors, this paper analyzes the number of supporting thermal units started, supporting unit power changed, wind power and connected substation power to find out the key factors of DC operating limit and wind power consumption. The validity of this paper was verified by a DC power grid simulation in a certain area.